GAMIFICATION IN FOREIGN LANGUAGE LEARNING: A BIBLIOMETRIC REVIEW - Wan Kamaruddin, Wan Anis Ilani; Abd Razak, Najjah Salwa; Ab Manan, Masdini Harina (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
Gamification has emerged as an innovative pedagogical approach in foreign language learning, enhancing learner engagement, motivation, and outcomes. This study conducts a bibliometric analysis to map the intellectual structure and research landscape of gamification in this domain. Data were retrieved from the Scopus database using the keywords gamification, teaching, learning, and language, yielding 1,239 documents refined through OpenRefine for accuracy. Scopus Analyzer provided insights into publication output, sources, citations, and contributing countries, while VOSviewer visualized co-authorship, keyword co-occurrence, and citation networks. Findings indicate a steady growth in research between 2015 and 2025, with a marked surge after 2018 and a peak in 2024. Spain, the United States, Indonesia, and Malaysia are identified as leading contributors, representing both established and emerging research hubs. Keyword analysis revealed seven thematic clusters encompassing gamification, e-learning, motivation, and language acquisition, alongside emerging areas such as artificial intelligence, virtual reality, and digital storytelling. Highly cited studies focused on systematic reviews, Duolingo, and gamified tools like Kahoot. Overall, the study highlights gamification as a rapidly expanding, interdisciplinary field and provides an overview of key publication trends and thematic directions to inform future research and pedagogical practice in language education.